Socio‐economic determinants and inequities in coverage and timeliness of early childhood immunisation in rural Ghana. Issue 7 (28th April 2014) - Gram, Lu; Soremekun, Seyi; ten Asbroek, Augustinus; Manu, Alexander; O'Leary, Maureen; Hill, Zelee; Danso, Samuel; Amenga‐Etego, Seeba; Owusu‐Agyei, Seth; Kirkwood, Betty R.
Abstract Objectives To assess the extent of socio‐economic inequity in coverage and timeliness of key childhood immunisations in Ghana. Methods Secondary analysis of vaccination card data collected from babies born between January 2008 and January 2010 who were registered in the surveillance system supporting the ObaapaVita and Newhints Trials was carried out. 20 251 babies had 6 weeks' follow‐up, 16 652 had 26 weeks' follow‐up, and 5568 had 1 year's follow‐up. We performed a descriptive analysis of coverage and timeliness of vaccinations by indicators for urban/rural status, wealth and educational attainment. The association of coverage with socio‐economic indicators was tested using a chi‐square‐test and the association with timeliness using Cox regression. Results Overall coverage at 1 year of age was high (>95%) for Bacillus Calmette–Guérin (BCG), all three pentavalent diphtheria‐pertussis‐tetanus‐haemophilus influenzae B‐hepatitis B (DPTHH) doses and all polio doses except polio at birth (63%). Coverage against measles and yellow fever was 85%. Median delay for BCG was 1.7 weeks. For polio at birth, the median delay was 5 days; all other vaccine doses had median delays of 2–4 weeks. We found substantial health inequity across all socio‐economic indicators for all vaccines in terms of timeliness, but not coverage at 1 year. For example, for the last DPTHH dose, the proportion of children delayed more than 8 weeks were 27% for urban children and 31% for rural children (P < 0.001), 21% in the wealthiest quintile and 41% in the poorest quintile (P < 0.001), and 9% in the most educated group and 39% in the least educated group (P < 0.001). However, 1‐year coverage of the same dose remained above 90% for all levels of all socio‐economic indicators. Conclusions Ghana has substantial health inequity across urban/rural, socio‐economic and educational divides. While overall coverage was high, most vaccines suffered from poor timeliness. We suggest that countries achieving high coverage should include timeliness indicators in their surveillance systems.